Determination of bone marrow cell morphology in rat: Bone marrow cell morphology - Jun Ling Shan,; Guang Yu Zhu,; Li Hui Su,; Xiao Song Liang,; Jun Fu,; Zhen Fen Zhang, (Cellular and Molecular Biology, 2023)
The skeletal system of the body is responsible for important functions in the human body. In addition to causing movement, this system also plays a role in the production of blood cells and fat storage. Bone marrow is a spongy or viscous tissue that fills the inside of the body's bones. The basic structure of bone marrow is of two types. Red bone marrow and yellow bone marrow. Red bone marrow contains blood stem cells that can become red blood cells, white blood cells, or platelets. Yellow bone marrow is made mostly of fat and contains stem cells that can turn into cartilage, fat, or bone cells. Human bone marrow mesenchymal stem cells (HBMSCs) are widely used cell sources for clinical bone regeneration. Achieving a therapeutic effect depends on the osteogenic differentiation potential of the stem cells. The purpose of judging the morphology of bone marrow cells is to diagnose leukemia or bone marrow disorders, determine the cause of severe anemia or thrombocytopenia and low platelet count, identify abnormal chromosomes to prevent hereditary diseases, and plan their treatment. In this study, we examined the morphological characteristics of bone marrow cells, mesenchyme cells, and osteoblasts in a laboratory environment. The results of the morphological investigations showed changes such as the change of the position of the nucleus and the rounding of the cytoplasm in the differentiated cells compared to the mesenchyme cells. Therefore, to identify and diagnose as many of these cells as possible, molecular genetic techniques such as network algorithms and fluorescence staining can be used for hematological and cytomorphological investigations.